Primary Pandemic Prevention. Issue 5 (September 2021) - Greger, Michael
Over the last few decades, hundreds of human pathogens have emerged at a rate unprecedented in human history. Emerged from where? Mostly from animals. The AIDS virus is blamed on the butchering of primates in the African bushmeat trade, we created mad cow disease when we turned cows into carnivores and cannibals, and SARS and COVID-19 have been traced back to the exotic wild animal trade. Our last pandemic, swine flu in 2009, arose not from some backwater wet market in Asia, however. It was largely made-in-the-USA on pig production operations in the United States. In this new Age of Emerging Diseases, there are now billions of animals overcrowded and intensively confined in filthy factory farms for viruses to incubate and mutate within. Today's industrial farming practices have given viruses billions more spins at pandemic roulette. How can we stop the emergence of pandemic viruses in the first place? Whenever possible, treat the cause. The largest and oldest association of public health professionals in the world, the American Public Health Association, has called for a moratorium on factory farming for nearly two decades. Indeed, factory farms are a public health menace. In addition to discontinuing the intensive confinement practices of animal agriculture, we should continue to research, develop, and invest in innovative plant-based and cultivated meat technologies to move away from raising billions of feathered and curly-tailed test tubes for viruses with pandemic potential to mutate within.